1992
DOI: 10.1093/infdis/165.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Appearance of Zidovudine Resistance Mutations during Treatment of 18 Human Immunodeficiency Virus-Positive Subjects

Abstract: The order of appearance in the reverse transcriptase gene of four mutations implicated in the development of resistance to zidovudine was investigated by selective polymerase chain reaction. Serial human immunodeficiency virus isolates were studied from 18 initially asymptomatic individuals who had been treated with zidovudine for 2 years. Most subjects had similar patterns. The first mutation occurred transiently at codon 70; its disappearance was paralleled by the appearance of a mutation at codon 215. Subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
192
2
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(206 citation statements)
references
References 16 publications
11
192
2
1
Order By: Relevance
“…If patients with viral failure are allowed to continue on first-line ART, then it is likely that resistance mutations will accumulate [4-6] and reduce the effectiveness of second-line ART [41]. …”
Section: Discussionmentioning
confidence: 99%
“…If patients with viral failure are allowed to continue on first-line ART, then it is likely that resistance mutations will accumulate [4-6] and reduce the effectiveness of second-line ART [41]. …”
Section: Discussionmentioning
confidence: 99%
“…15 In the zidovudine group, the previously reported pattern of appearance of mutations was seen with rapid occurrence of the K70R substitution followed by a concomitant rise in the T215Y/F mutation and reciprocal loss of the K70R mutant. 16 The M41L mutation evolved more slowly. By contrast, in both combined-therapy groups the initial emergence of K70R was not seen, and M41L and T215Y/F mutations evolved more rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The Amsterdam asymptomatic cohort studied consisted of 18 high-risk (CD4 < 500) HIV-infected individuals of whom 17 were studied (Boucher et al, 1992a). From this cohort two individuals, Patient 199 (Pt199) and Patient 105 (Pt105), for whom multiple, sequential, cryopreserved PBL samples were available were chosen for detailed genetic analysis of viral zidovudine resistance.…”
Section: Methodsmentioning
confidence: 99%
“…The relative sensitivities of certain combinations of these mutations have been reported . The appearance of the four amino acid substitutions has been studied in an asymptomatic patient population (Boucher et al, 1992a); this revealed an ordered but complex pattern of mutation acquisition. The substitution of Arg-70 ~ Lys is commonly detected first during zidovudine treatment.…”
Section: Introductionmentioning
confidence: 99%